Все публикации

Laplace Transform of e^(-t)cos(3t) + e^(6t) - 1

Laplace Transform of 3t^2 - e^(2t)

Laplace Transform of t^2 + e^t sin(2t)

How To Graph ALL Step Functions

y'' + 4y = csc^2(2t)

y'' + 4y' + 4y = e^(-2t)ln(t)

y'' + 9y = sec^2(3t)

y'' + 16y = sec(4x)

y'' + 2y' + y = e^(-t)

y'' - 2y' + y = t^-1e^t

y'' + y = sec(t)

y'' + 4y = tan(2t)

Integral of (x+2)(3x^2+12x+1)^1/2 from 0 to 1

y'' + y = 4xcos(x)

y'' - 5y' + 6y = xe^x

2z'' + z = 9e^(2t)

y'' - y' + 9y = 3sin(3t)

2x' + x = 3t^2

y''(x) + y(x) = 2^x

y'' + 2y' - y = 10

y'' + 3y = -9

Converting a Riemann Sum to a Definite Integral

4y'' - 4y' + 26y = 0

4y'' + 4y' + 6y = 0